Hospital-Acquired Staphylococcus aureus in Thi-Qar Governorate: A Molecular and Epidemiological Perspective - Ali, Alaa; Saad S. Hamim; Hamzah Shakir (University of Thi-Qar Journal of Science, 2025)
Staphylococcus aureus (S. aureus) is a pathogenic strain of bacteria, that resists multiple multi-antibiotics used for common bacterial infections. Most S. aureus infections occur among people consulting hospitals or other healthcare settings such as nursing homes and dialysis centers. This study aimed to molecularly identify S. aureus strains associated with nosocomial infections in hospitals of Thi-Qar. A total of 100 samples were collected from various locations in three hospitals in Thi-Qar Governorate. Polymerase Chain Reaction (PCR) technique was utilized to assay the presence of S. aureus via 16S rRNA gene. The study population consisted of both male and female patients, with a male predominance (82% males vs. 18% females), showing statistically significant differences (p ≤ 0.01). The highest frequency of isolates (65%) was observed in the 21–31 age group, which also demonstrated a significant difference compared to other age groups. The PCR amplification of the 16S rRNA gene was successfully submitted to GenBank and assigned the accession numbers LC866513, LC866514, and LC866515. Phylogenetic analysis using MEGA-10 software revealed distinct molecular relationships between the local S. aureus isolates and genetically related strains from various regions worldwide. The outcomes of this study provide valuable insights that could inform and enhance infection control practices, thereby contributing to the mitigation of disease transmission within healthcare environments.